Performance of commercial laying hen submitted to different debeaking methods - Oka, C. H. [UNESP] (2017)
Among the several factors required in breeding laying hens, debeaking is a factor that interferes with batch performance and affects animal welfare. Thus, the objective of this study was to evaluate three different debeaking procedures and to verify the best technique to be used. For this, the performance of the birds, the incidence of cannibalism, and in rearing phase, the quality of the eggs were evaluated. Dekalb White birds were distributed in a completely randomized design with three treatments, T1 (infrared radiation debeaking) T2 (hot blade debeaking) and T3 (V debeaking).The data was submitted to Analysis of Variance and compared by Tukey’s test (95%), using statistical software R. The frequencies of mortality and cannibalism were submitted to the Chi-Square test (Software R). It was observed that mortality was lower with IR debeaking in the breeding phase. Already in the rearing phase, the mortality was similar between the debeaking techniques and the cannibalism was null. The final mean weight (g), mean weight gain (g) and average daily weight gain in the rearing and egg quality variables were higher for V debeaking when compared to other techniques. It is concluded that V-debeaking provides better bird performance, resistance and shell thickness when compared to the infrared radiations and hot blade debeaking, in addition to subjecting the birds to less stress.